The effect of competency, education and training, workload on functional employee performance with work motivation as a variable intervening at regional government secretariat of the Riau Island Province - Muhammad Tabrani; Bambang Satriawan; Mohammad Gita Indrawan (Journal of Multidisciplinary Academic Business Studies, 2024)
Purpose: This study aimed to examine the influence of competence, education and training, and workload on functional employee performance, with work motivation as an intervening variable, at the Regional Secretariat of the Riau Islands Provincial Government. Research Methodology: A quantitative approach was applied using census sampling of all 106 employees. Data were collected through questionnaires and analyzed using Partial Least Square (PLS) with SmartPLS 4.0 to evaluate the measurement and structural models. Results: The findings revealed that competence, education and training, workload, and work motivation each had positive and significant effects on employee performance. Competence, education, and training did not significantly influence work motivation, whereas workload showed a positive and significant impact. Work motivation successfully mediated the effects of competence, education and training, and workload on employee performance. The model explained 59.6% of the performance variance and 49.2% of the motivation variance. Conclusions: Functional employee performance is shaped not only by technical competence and training but also by workload management and motivation. Work motivation plays a crucial mediating role in linking employee attributes and organizational outcomes. Limitations: The study is limited to one regional government office; therefore, the results may not fully represent other public sector institutions or different organizational settings. Contribution: This study highlights the mediating role of motivation in public sector employee performance and offers practical guidance for improving training, workload distribution and motivational strategies.